Guinea : Enhanced Initiative for Heavily Indebted Poor Countries-Completion Point Document and Multilateral Debt Relief Initiative. (IMF Staff Country Reports; Country Report ;, 2012)
This paper was prepared by staffs of the International Monetary Fund and the World Bank in connection with the Executive Board's consideration of Guinea's Completion Point under the Enhanced Initiative for Heavily Indebted Poor Countries and debt relief under the Multilateral Debt Relief Initiative. It is based on the information available at the time it was completed on September 11, 2012. The views expressed in this document are those of the staff team and do not necessarily reflect the views of the government of Guinea or the Executive Board of the IMF.